Quantitative Environmental Risk Analysis for Human Health - Asvapathanagul, Pitiporn (Journal of Architectural/Planning Research and Studies (JARS), 2022)
This current comprehensive publication byFjeld et al., (2007) aims to provide integral knowledgerelated to the analysis of environmental humanhealth risks which consequently come from areconsequences of human activities in a variety ofscales. This work contains all three componentsmandatorily required in environmental risk analysis,including risk assessment, risk management andrisk communication. However, the textbook mainlyfocuses on the computation of risk assessment.